2007
DOI: 10.1016/j.archoralbio.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prism orientation on the indentation testing of human molar enamel

Abstract: Recent nanoindentation studies have demonstrated that the hardness and Young's modulus of human molar enamel decreases by more than 50% on moving from the occlusal surface to the dentin-enamel junction on cross-sectional samples. Possible sources of these variations are changes in local chemistry, microstructure, and prism orientation. This study investigates the latter source by performing nanoindentation tests at two different orientations relative to the hydroxyapatite prisms: parallel and perpendicular. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 22 publications
6
70
1
6
Order By: Relevance
“…The use of AFM provided a convenient in situ observation of the indentation, which allowed us to improve the reliability of the data based on the indentation morphology. The mean values of the elastic modulus and the hardness and their aging-and location-induced changes were consistent with previous investigations (Cuy et al, 2002;Braly et al, 2007;Park et al, 2008b).…”
Section: Discussionsupporting
confidence: 79%
“…The use of AFM provided a convenient in situ observation of the indentation, which allowed us to improve the reliability of the data based on the indentation morphology. The mean values of the elastic modulus and the hardness and their aging-and location-induced changes were consistent with previous investigations (Cuy et al, 2002;Braly et al, 2007;Park et al, 2008b).…”
Section: Discussionsupporting
confidence: 79%
“…The standard deviation of hardness in this study showed a broad variation, similar to previous reports 16 . This broad variation of hardness values can be produced by factors such as specimen preparation, diagonal length reading error 16 , variation in chemical composition 20 , age, and location in the tooth 21 . In this study, the KHN and VHN values of enamel are in approximately the same range, while dentin obtained KHN values higher than VHN values for every variation of indentation load and time.…”
Section: Discussionmentioning
confidence: 99%
“…X, calcium substitution with metal cation; Y, phosphate substitution with carbonate; and Z, hydroxide substitution with fluoride. [55][56][57] Ca 5 (PO 4 ) 3 (OH)…”
Section: Role Of Calcium and Phosphate Ions In Teeth And Bonementioning
confidence: 99%